Association of Corporate Performance and Supply Chain Management: A Competitive Advantage Perspective - Wahyu Anggit Prasetya; Fira Sofana Tuzzahrok; Rochiyati Murniningsih (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
The purpose of this study was to examine the effect of supply chain management on company performance with competitive advantage as a mediating variable in Micro, Small and Medium Enterprises (MSMEs). The sample in this study used culinary SMEs as the object of research. While the method used in sampling is purposive sampling. Samples were taken as many as 344 respondents with the criteria of culinary SMEs in Magelang Regency which had a minimum workforce of 5 people and the business was over 2 years old. The analytical tool used is path analysis using SmartPLS 3.0 software. The results show that supply chain management and competitive advantage partially have a positive effect on company performance, supply chain management has a positive effect on competitive advantage, and competitive advantage has an effect on company performance, and competitive advantage can mediate supply chain management relationships on company performance.